Associations of HbA1c with the timing of C‐peptide responses during the oral glucose tolerance test at the diagnosis of type 1 diabetes. Issue 4 (15th April 2019) - Ismail, Heba M.; Evans‐Molina, Carmella; DiMeglio, Linda A.; Becker, Dorothy J.; Libman, Ingrid; Sims, Emily K.; Boulware, David; Herold, Kevan C.; Rafkin, Lisa; Skyler, Jay; Cleves, Mario A.; Palmer, Jerry; et al.
Abstract : Background: In new onset type 1 diabetes (T1D), overall C‐peptide measures such as area under the curve (AUC) C‐peptide and peak C‐peptide are useful for estimating the extent of β‐cell dysfunction, and for assessing responses to intervention therapy. However, measures of the timing of C‐peptide responsiveness could have additional value. Objectives: We assessed the contribution of the timing of C‐peptide responsiveness during oral glucose tolerance tests (OGTTs) to hemoglobin A1c (HbA1c) variation at T1D diagnosis. Methods: We analyzed data from 85 individuals <18 years with OGTTs and HbA1c measurements at diagnosis. Overall [AUC and peak C‐peptide] and timing measures [30‐0 minute C‐peptide (early); 60 to 120 minute C‐peptide sum‐30 minutes (late); 120/30 C‐peptide; time to peak C‐peptide] were utilized. Results: At diagnosis, the mean (±SD) age was 11.2 ± 3.3 years, body mass index (BMI)‐z was 0.4 ± 1.1, 51.0% were male. The average HbA1c was 43.54 ± 8.46 mmol/mol (6.1 ± 0.8%). HbA1c correlated inversely with the AUC C‐peptide ( P  < 0.001), peak C‐peptide ( P  < 0.001), early and late C‐peptide responses ( P  < 0.001 each), and 120/30 C‐peptide ( P  < 0.001). Those with a peak C‐peptide occurring at ≤60 minutes had higher HbA1c values than those with peaks later ( P  = 0.003). HbA1c variance was better explained with timing measures added to regression models ( R 2  = 11.6% with AUC C‐peptide alone; R 2  = 20.0% with 120/30 C‐peptide added; R 2  = 13.7% with peak C‐peptide alone, R 2  = 20.4% with timing of the peak added). Similar associations were seen between the 2‐hour glucose and the C‐peptide measures. Conclusions: These findings show that the addition of timing measures of C‐peptide responsiveness better explains HbA1c variation at diagnosis than standard measures alone.